2022
DOI: 10.3390/ijms23031799
|View full text |Cite
|
Sign up to set email alerts
|

Broad Spectrum Anti-Bacterial Activity and Non-Selective Toxicity of Gum Arabic Silver Nanoparticles

Abstract: Silver nanoparticles (AgNPs) are the most commercialized nanomaterials and presumed to be biocompatible based on the biological effects of the bulk material. However, their physico-chemical properties differ significantly to the bulk materials and are associated with unique biological properties. The study investigated the antimicrobial and cytotoxicity effects of AgNPs synthesized using gum arabic (GA), sodium borohydride (NaBH4), and their combination as reducing agents. The AgNPs were characterized using ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 81 publications
(116 reference statements)
2
24
0
Order By: Relevance
“…Several studies have demonstrated the potential anti-cancer activity of AgNPs, including AgNPs synthesized from various plant extracts [ 23 ]. Table 5 highlights some of the plant-synthesized AgNPs and their anti-cancer effects on multiple cancer cell lines, namely breast (MCF-7) [ 110 ], lung (A549) [ 111 ], cervical (HeLa) [ 112 ], colon (HT-29, Caco-2) [ 113 ], prostate (PC-3) [ 26 ], and VCaP [ 114 ] cancer cell lines. The half-maximal inhibitory concentration (IC 50 ) of AgNPs was comparable to that of standard anti-cancer drugs [ 23 ] and a validation that AgNPs could be useful as anti-cancer agents.…”
Section: Biomedical Applications Of Biogenic Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the potential anti-cancer activity of AgNPs, including AgNPs synthesized from various plant extracts [ 23 ]. Table 5 highlights some of the plant-synthesized AgNPs and their anti-cancer effects on multiple cancer cell lines, namely breast (MCF-7) [ 110 ], lung (A549) [ 111 ], cervical (HeLa) [ 112 ], colon (HT-29, Caco-2) [ 113 ], prostate (PC-3) [ 26 ], and VCaP [ 114 ] cancer cell lines. The half-maximal inhibitory concentration (IC 50 ) of AgNPs was comparable to that of standard anti-cancer drugs [ 23 ] and a validation that AgNPs could be useful as anti-cancer agents.…”
Section: Biomedical Applications Of Biogenic Agnpsmentioning
confidence: 99%
“…Although the biogenic AgNPs are considered to have a reduced risk of toxicity compared with cAgNPs, they are also non-selective. The toxicity of biogenic AgNPs is also influenced by a number of parameters, among others being the size [ 113 ].…”
Section: Perspectives and Concerns For Clinical Application Of Agnpsmentioning
confidence: 99%
“…Thus, conjugation of AgNPs to HAART may exert significant benefits, such as reducing the dosage of HAART needed for therapy and inhibiting some pathophysiological mechanisms mediated by HAART in contribution to diabetes ( Lawal et al, 2021 , Olojede et al, 2022 ). Although, the issues related to the toxicity profile of AgNPs on the biological tissues have been raised ( Fadaka et al, 2022 ). Conversely, studies have reported that the toxicity profile of AgNPs depends on several factors such as nanoparticles size, shape, morphology, dimension, and capping agent ( Alkaladi et al, 2014 , Fadaka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, the issues related to the toxicity profile of AgNPs on the biological tissues have been raised ( Fadaka et al, 2022 ). Conversely, studies have reported that the toxicity profile of AgNPs depends on several factors such as nanoparticles size, shape, morphology, dimension, and capping agent ( Alkaladi et al, 2014 , Fadaka et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gum arabic was deemed to be the most effective reducing agent in improving the bactericidal efficiency of the synthesized silver nanoparticles. However, the authors concluded that the nanoparticle toxicity could not be completely overcome, even by using a greener synthesis methodology, which is required in order to establish ranges of effectiveness for human safety [ 9 ]. Novel aminothiazoles with superior antiviral, antioxidant, and antibacterial activities were also synthesized by Minickaitė et al They demonstrated that, by using substitutes in the thiazole ring, optimized antimicrobial structures could be generated with target specificity [ 10 ].…”
mentioning
confidence: 99%